Essays on judicial behavior - Lopes, Felipe de Mendonça (2018)
What do judges want? Although apparently a straightforward question, the motivations that underly judge’s decisions have been a persistent topic of debate in the literature. The discussion arises from the fact that judges, especially those in superior courts, are usually insulated from the ordinary incentives that other agents face. Most enjoy life tenure, their salaries cannot be decreased, and have no performance bonus. Hence, an assumption of economic self-interest would hardly provide useful insights into judicial preferences. In the three essays that form this thesis, I contribute to the judicial behavior literature by providing empirical evidence of at least three different vectors that govern judicial decision-making. In the first essay, I show that judges respond to transparency and scrutiny. The main idea is to explore how a shift in transparency – since 2002 the Brazilian Supreme Court (STF) broadcasts its deliberations live on television – may alter behavior. Here, I employ a research design seldom used in the judicial behavior literature – Differences-in-Differences – to test how STF judges have responded to increased transparency. The main finding is that STF justices, when given free television time, act to maximize their individual exposure. They achieve that by writing longer votes and by engaging in more discussions with their peers. In the second essay, I show that political preferences matter. Here, in delving into the judicial activism literature, I test whether activism is related to politics in two ways. First, whether judges appointed by left-wing presidents are more (or less) likely to engage in activist voting than those appointed by right-wing presidents. Second, if judges appointed by presidents of either end of the political spectrum are sensitive to political context, that is, if they respond to the presence of their appointing party in the Executive. In doing so, I propose a new measure of judicial activism, which conditions votes to strike on the Prosecutor-General’s brief. The main result is that activism – both in the traditional and new measures – is associated with ideology measured by presidential appointment. Also, in the new measure, judges are sensitive to political context – they are less likely to engage in activist voting when their appointing party is incumbent in the Federal Executive. Lastly, career matters. Justices that are former politicians are less likely to be activist. Finally, in the third essay, I investigate the determinants of judicial dissent in the Brazilian Supreme Court. Particularly, I disentangle two features of judicial behavior that are known to affect the decision to dissent: ideological heterogeneity and dissent aversion. To do so, I explore the fact that voting in this Court is sequential, that there is a predetermined voting order that varies in nearly every case, to identify where dissent aversion will manifest. The main point is that after a majority has been formed, the justices who vote in sequence know that their votes cannot change the outcome of the case. Hence, they may deviate from their preferred votes and join the majority to avoid the costs of dissenting. Here, I find strong evidence of dissent aversion in the Brazilian Supreme Court. Judges who vote after the pivotal judge are significantly less likely to dissent. The evidence for ideology, however, does not survive all robustness checks.